Applications of aluminum sustain growth of strawberry (Fragaria × ananassa Duch.) supplemented with phosphoric rock in soilless culture. - Valdez Aguilar, Luis Alonso; Tucuch Pérez, Martín Alejandro; Hernández Pérez, Armando; Pérez Arias, Gloria Alicia; García Santiago, Juana Cruz; Alvarado Carrillo, Daniela (REVISTA TERRA LATINOAMERICANA, 2017)
It is estimated that in the near future phosphorus (P) sources for manufacturing fertilizers containing this element will become scarce. Phosphorus can be found in the soil; however, it is not in soluble form for plant uptake. In order to take up this element, plants exude organic acids (OA), which can facilitate the solubilization of P. It has been reported that these acids are exuded into the rhizosphere in the presence of aluminum (Al). Given the solubilizing capacity of OA, the present study was designed to assess the effect of using Al on exudation of OA, which in turn would improve root uptake of insoluble P forms, impacting growth and yield of strawberry plants. The experiment consisted of eight treatments that resulted from combining two amounts of phosphoric rock (PR), mixed in the substrate, with applications of Al. The treatments with PR were irrigated with nutrient solutions containing 0.25 meq L‑1 H2PO4‑. Application of Al through the irrigation solution produced the highest yields, up to 380 g plant-1. There was also a positive correlation between yield and citrate concentration and a negative correlation between yield and malate concentration in the substrate. We conclude that increased citrate in the rhizosphere due to the presence of Al increased solubility of PR, thus increasing yield.